Synthesis and Properties of (Bi, Cd)-doped CuMn2O4 thin films by sol-gel dip-coating method - Kharroubi, Abdelmalek; Khiali, Aboulkacem; Benhebal, Hadj; Benrabah, Bedhiaf; Lellou, Salima; Kadi, Samir; Sadouki, Bellal (Physics and Chemistry of Solid State, 2021)
The present work is carried out within the framework of a research project launched within the physical engineering laboratory at the University of Tiaret in Algeria. The objective is to optimize the conditions for producing thin films of pure spinel oxides doped with different metallic elements. Thus, in this part, we prepared thin films of pure CuMn2O4 and doped with Bi and Cd at rates of 6 and 9% by the sol-gel Dip-coating method. The materials obtained exhibit acceptable crystallinity, excellent optical transmittance with bandgap energies of between 1.64 eV and 1.9 eV and good electrical conductivity.